More plant growth but less plant defence? First global gene expression data for plants grown in soil amended with biochar. Issue 4 (26th March 2014) - Viger, Maud; Hancock, Robert D.; Miglietta, Franco; Taylor, Gail
Abstract Biochar is a carbon (C)‐rich solid formed when biomass is used to produce bioenergy. This 'black carbon' has been suggested as a solution to climate change, potentially reducing global anthropogenic emissions of greenhouse gases by 12%, as well as promoting increased crop growth. How biochar application to soil leads to better crop yields remains open to speculation. Using the model plant Arabidopsis and the crop plant lettuce (Lactuca sativa L.), we found increased plant growth in both species following biochar application. Statistically significant increases for Arabidopsis in leaf area (130%), rosette diameter (61%) and root length (100%) were observed with similar findings in lettuce, where biochar application also increased leaf cell expansion. For the first time, global gene expression arrays were used on biochar‐treated plants, enabling us to identify the growth‐promoting plant hormones, brassinosteroid and auxin, and their signalling molecules, as key to this growth stimulation, with limited impacts on genes controlling photosynthesis. In addition, genes for cell wall loosening were promoted as were those for increased activity in membrane transporters for sugar, nutrients and aquaporins for better water and nutrient uptake and movement of sugars for metabolism in the plant. Positive growth effects were accompanied by down‐regulation of a large suite of plant defence genes, including the jasmonic acid biosynthetic pathway, defensins and most categories of secondary metabolites. Such genes are critical for plant protection against insect and pathogen attack, as well as defence against stresses including drought. We propose a conceptual model to explain these effects in this biochar type, hypothesizing a role for additional K+ supply in biochar amended soils, leading to Ca2+ and Reactive Oxygen Species (ROS) –mediated signalling underpinning growth and defence signalling responses.